A Comparative Study on the Effects of Planarity of Access Region on the Low-Frequency Noise Performance of InAlN/GaN HFETs - Yatexu Patel; Pouya Valizadeh (IEEE Journal of the Electron Devices Society)
The low frequency drain noise-current characteristics of metallic-face InAlN/AlN/GaN heterostructure field effect transistors (HFETs) having fin structures only under the gate, while maintaining a planar structure in the access regions, are compared to those of the HFETs having fin structures stretched from source to drain. Evidence indicates that both device types follow the trends of carrier number fluctuation (CNF) with correlated mobility fluctuation (CMF) model of 1/f noise. Accordingly, the noise of the gated channel has been identified as the dominant noise source for both device types. Devices from the former category exhibit improved 1/f noise performance with lower drain noise-current spectral density. This observation could be due to presence of a higher two-dimensional electron gas (2DEG) concentration under the gated-channel overshadowing the carrier number and mobility fluctuations.